2023
DOI: 10.3390/ijms24044192
|View full text |Cite
|
Sign up to set email alerts
|

Identifying SARS-CoV-2 Drugs Binding to the Spike Fatty Acid Binding Pocket Using In Silico Docking and Molecular Dynamics

Abstract: Drugs against novel targets are needed to treat COVID-19 patients, especially as SARS-CoV-2 is capable of rapid mutation. Structure-based de novo drug design and repurposing of drugs and natural products is a rational approach to discovering potentially effective therapies. These in silico simulations can quickly identify existing drugs with known safety profiles that can be repurposed for COVID-19 treatment. Here, we employ the newly identified spike protein free fatty acid binding pocket structure to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Oxabolone and Selexipag have been identified in two separate virtual screening studies directed at the FABP, based on the LA cocrystallized structure (PDB ID: 6ZB5 and 6ZB4), and libraries of approved drugs. , However, none of these studies assessed biological activity or determined binding affinities with the S protein; therefore, they still require validation for the virtual screening campaigns performed. As expected, the reported predicted binding and pocket occupation follows patterns previously identified, with oxabolone predicted to interact as SPC-14, whereas selexipag contains three aromatic rings and a flexible chain that extends toward the hydrophilic residues in the pocket. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxabolone and Selexipag have been identified in two separate virtual screening studies directed at the FABP, based on the LA cocrystallized structure (PDB ID: 6ZB5 and 6ZB4), and libraries of approved drugs. , However, none of these studies assessed biological activity or determined binding affinities with the S protein; therefore, they still require validation for the virtual screening campaigns performed. As expected, the reported predicted binding and pocket occupation follows patterns previously identified, with oxabolone predicted to interact as SPC-14, whereas selexipag contains three aromatic rings and a flexible chain that extends toward the hydrophilic residues in the pocket. , …”
Section: Resultsmentioning
confidence: 99%
“…As expected, the reported predicted binding and pocket occupation follows patterns previously identified, with oxabolone predicted to interact as SPC-14, whereas selexipag contains three aromatic rings and a flexible chain that extends toward the hydrophilic residues in the pocket. 62,63 In summary, six additional compounds were identified as potential ligands to the FABP, based on their predicted interactions with the S protein, described in the original virtual screening studies that explored these chemical entities. Upon analysis of these molecules for their binding to the FABP using a molecular docking procedure, only for two of these potential ligands, rotiorinol C and hyoscyamine, favorable binding poses to this site could be observed.…”
Section: Retinoids and Lipid-soluble Vitaminsmentioning
confidence: 99%
“…Casalino et al [25] investigated the multifaceted roles of glycans in spike viral entry and immune recognition, while Kapoor et al [26] highlighted the impact of posttranslational modifications on spike glycoprotein interactions with host cell receptors. Wang et al [5] and Piplani et al [27] utilized in silico techniques to identify small molecules targeting the spike's conserved FFA binding pocket as a starting point for broadspectrum COVID-19 treatments. Shoemark et al [28] examined the effects of LA and other ligands when bound to the spike FFA binding pocket, revealing insights into conformational stability.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Specifically, antigenic T-cells prepared by the IFN-γ cytokine capture system (CCS) have been classified as ATMPs, authorized for intended use by the EMA, and are currently used in critically ill SARS-CoV-2 patients. Another study conducted by Piplani et al [ 11 ] and Barakat et al [ 12 ] showed promising evidence regarding the design and synthesis of modern compounds targeting either the ACE2 receptor or the replication machinery of SARS-CoV-2. Moreover, Lee et al [ 13 ] reported the beneficial role of compounds that can downregulate specific signaling pathways, such as the sterile alpha motif, histidine-aspartate domain-containing protein 1 (SAMHD1) tetramerization and the cytosolic DNA sensor cyclic-GMP–AMP synthase (cGAS), as a stimulator of interferon gene (STING) signaling pathways.…”
mentioning
confidence: 99%